Pattern of Mental Disorders among the Students of the University of Gezira- Sudan - Elhadi, Magda; Mohamed, Khatab; M Haroon, Huda; Ahmed, Fathia Omer; Abubakr, Dia eldeen Elgiali (Gezira Journal of Health Sciences, 2015)
This retrospective study was conducted in the University of Gezira (U of G) - Sudan, in the year 2009. The objective of the study was to describe the pattern of mental disorders among the students of (U of G) and to assess the services provided for them. The data of 200 students suffering from mental disorders, total coverage, was obtained by reviewing the records of the health services of the university, interview with the Director General of Psychiatry and Mental Health Hospital and with the psychologist responsible for dealing with students suffering from mental disorders.  The results revealed the following: the prevalence of mental disorders among the students of (U of G) was found to be (0.8%), more than half (51.5%) were females, male students were (48.9%), (57.5%) of them were residing outside Medani. Regarding their tribes the majority were from Galli tribe the other tribes were all represented with different rates. The following types of mental disorders described among the students, depression (42%), dissociative (23%), Schizophrenia (13%), Mania (6.5%), Epilepsy (9%), Anxiety (3%), Headache (2.5%).The faculty of Computer and Mathematic of sciences showed a big number of mental disorder stud ents compared to the other faculties.  The study also showed lack of close follow up from the students themselves and their families. A problem of continuation of the treatment was observed. The study recommended; special mental health unit in the different faculties, Free drugs for mental disorders, Provision of mental health promotional services at the university including mental health education and screening services.